Pengaruh Profitabilitas, Kepemilikan Manajerial Dan Institusional Terhadap Pengungkapan Tanggung Jawab Sosial Perusahaan Di Industri Jasa - Mardiati, Endang; LH, Laila Fitriyah (JRAM (Jurnal Riset Akuntansi Multiparadigma), 2024)
This research aims to test and analyze the influence of leverage, managerial ownership, institutional ownership on CSR disclosure in sustainability reports through profitability as a mediating variable. The object of this research is service sector companies listed on the IDX. A total of 45 data were collected using the purposive sampling method. Data analysis was carried out using regression analysis using the SPSS 24 application. The test results showed that leverage and institutional ownership had a positive effect on profitability, while managerial ownership had no significant effect on profitability. Profitability itself influences CSR disclosure. Based on this, profitability can mediate the relationship between leverage and CSR disclosure, but cannot mediate the relationship between managerial ownership and managerial institutional ownership and CSR disclosure.